2018
DOI: 10.1590/0102.3772e33421
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Brief Intervention based on Motivational Interviewing in Colombian Adolescents

Abstract: -Prevention science has identifi ed evidence-based strategies for reducing alcohol and other drug use among adolescents, such as Brief Interventions (BI) and Motivational Interviewing (MI). However, there is little evidence about the eff ectiveness of these practices in Colombia. This study aimed to analyze the eff ectiveness of the preventive program Brief Intervention based on Motivational Interviewing (BIMI) in reducing alcohol use in adolescents. The program was administered to 3,159 secondary students thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Several studies considered the use of BI among vulnerable populations in LA. Studies from Mexico, Argentina, Brazil, and Colombia evaluated the use of BI among adolescent populations [56][57][58][59][60][61][62], but evidence is mixed and limited in terms of representativeness of the samples. For instance, the few randomized controlled trials [60,62] vary with regard to the number of BI sessions (from one to four) and sample sizes (ranging from 25 to 58).…”
Section: Demand Side Supply Sidementioning
confidence: 99%
“…Several studies considered the use of BI among vulnerable populations in LA. Studies from Mexico, Argentina, Brazil, and Colombia evaluated the use of BI among adolescent populations [56][57][58][59][60][61][62], but evidence is mixed and limited in terms of representativeness of the samples. For instance, the few randomized controlled trials [60,62] vary with regard to the number of BI sessions (from one to four) and sample sizes (ranging from 25 to 58).…”
Section: Demand Side Supply Sidementioning
confidence: 99%
“…The results demonstrated that BIMI serves as a preventive strategy, effectively reducing the frequency and quantity of alcohol consumption among adolescents. The study further investigated the impact of elapsed time between sessions on the outcomes, providing valuable insights for prevention and evaluation methodologies [ 12 ]. This highlights the significance of incorporating MI-based interventions in adolescent alcohol reduction programs, emphasizing the potential for positive behavioural changes and improved well-being.…”
Section: Introductionmentioning
confidence: 99%
“…IBEM -U is an online prevention program for university students and is based on our previously created and evaluated face-to-face IBEM program for adolescents; IBEM showed significant effects on decreasing alcohol consumption [ 33 , 34 ]. A pilot was conducted in 2020 with 60 students, and adjustments were made mainly to the platform.…”
Section: Introductionmentioning
confidence: 99%